Doing Business in Punjab : An Agenda for Sub-National Reform - World Bank (Washington, DC, 2015)
This report examines the Doing Business database for 6 cities in Pakistan in order to assess how cities in the Punjab – Lahore, Faisalabad and Sialkot, may hypothetically improve their global rankings, as defined by the Doing Business methodology, by adopting the policies, regulations and practices of other cities in Pakistan. The report attempts to distinguish between those areas which are related to policies and regulations from those which are based on proximity, cost of services and court efficiency in order to provide specific guidance to policy makers regarding areas where improvements are possible.